Blockchain Technology and Its Potential Effects on Accounting: A Systematic Literature Review - ATİK YILDIRIM, ASUMAN (ISTANBUL UNIV, SCH BUSINESS, 2021)
With the growth of the business world, autonomous software programs such as MRP, ERP, and SAP have been used to synchronize different units and departments since the 1960s. There have been great technological developments in the last decades, such as Blockchain, the Internet of Things, artificial intelligence, and machine learning. The attention of the accounting world has also been on those technological developments, especially on Blockchain Technology. Accounting academics and professionals have been trying to understand how blockchain technology can affect accounting and what kind of changes might be brought about by that technology. Therefore, the purpose of this study is to make a systematic literature review in order to foresee the potential effects of blockchain on accounting. Selected keywords were searched for on the Scopus database. The results show that most of the studies in this area focus on technical issues and the development of software applications, and a small number of studies make a connection between blockchain and accounting. Although most of the authors are very optimistic about blockchain technology and claim that this technology may change the double-entry accounting system completely and radically, some have discrete approach and express critical views.
Keywords: Blockchain; Cryptocurrency; Accounting; Auditing